Differences in mutagenic and recombinational DNA repair in enterobacteria. - Sedgwick, S G (1985)
The incidence of recombinational DNA repair and inducible mutagenic DNA repair has been examined in Escherichia coli and 11 related species of enterobacteria. Recombinational repair was found to be a common feature of the DNA repair repertoire of at least 6 genera of enterobacteria. This conclusion is based on observations of (i) damage-induced synthesis of RecA-like proteins, (ii) nucleotide hybridization between E. coli recA sequences and some chromosomal DNAs, and (iii) recA-negative complementation by plasmids showing SOS-inducible expression of truncated E. coli recA genes. The mechanism of DNA damage-induced gene expression is therefore sufficiently conserved to allow non-E. coli regulatory elements to govern expression of these cloned truncated E. coli recA genes. In contrast, the process of mutagenic repair, which uses umuC+ umuD+ gene products in E. coli, appeared less widespread. Little ultraviolet light-induced mutagenesis to rifampicin resistance was detected outside the genus Escherichia, and even within the genus induced mutagenesis was detected in only 3 out of 6 species. Nucleotide hybridization showed that sequences like the E. coli umuCD+ gene are not found in these poorly mutable organisms. Evolutionary questions raised by the sporadic incidence of inducible mutagenic repair are discussed.